2018
DOI: 10.1002/tcr.201800141
|View full text |Cite
|
Sign up to set email alerts
|

Development of Divide‐and‐Conquer Density‐Functional Tight‐Binding Method for Theoretical Research on Li‐Ion Battery

Abstract: The density‐functional tight‐binding (DFTB) method is one of the useful quantum chemical methods, which provides a good balance between accuracy and computational efficiency. In this account, we reviewed the basis of the DFTB method, the linear‐scaling divide‐and‐conquer (DC) technique, as well as the parameterization process. We also provide some refinement, modifications, and extension of the existing parameters that can be applicable for lithium‐ion battery systems. The diffusion constants of common electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 109 publications
(134 reference statements)
0
21
0
Order By: Relevance
“…That is to say that the extremely non-uniform hopping integrals that are associated with various orbital hybridizations are rather difficult to achieve in order to t the main features of the rst-principles band structure. It seems that obtaining a reliable tight-binding model in Li + -based anode, 73 cathode 73 and electrolyte materials 73 will become an open issue, since it is relatively easy to understand the essential physical/material/chemical properties 74 from the concise pictures.…”
Section: Rich and Unique Electronic Propertiesmentioning
confidence: 99%
“…That is to say that the extremely non-uniform hopping integrals that are associated with various orbital hybridizations are rather difficult to achieve in order to t the main features of the rst-principles band structure. It seems that obtaining a reliable tight-binding model in Li + -based anode, 73 cathode 73 and electrolyte materials 73 will become an open issue, since it is relatively easy to understand the essential physical/material/chemical properties 74 from the concise pictures.…”
Section: Rich and Unique Electronic Propertiesmentioning
confidence: 99%
“…The benchmark calculations showed that simulation of one MD step for water system consisting of a few millions of atoms is completed within minutes using more than one hundred thousands of cores . The developed program has acquired robustness to the reactive system by means of grid box type fragments and enabled QM‐based MD simulations for systems consisting of from hundreds to thousands of atoms routinely when using laboratory workstation and/or moderate computer resources …”
Section: Introductionmentioning
confidence: 99%
“…[52] The developed program has acquired robustness to the reactive system by means of grid box type fragments and enabled QM-based MD simulations for systems consisting of from hundreds to thousands of atoms routinely when using laboratory workstation and/or moderate computer resources. [53][54][55][56][57][58][59][60][61] Although the parallelized DC-DFTB calculation has bridged the gap of system size existing between QM-based and classical MD simulations, further integrating advanced extensions into the program is necessary to allow the user to facilitate his or her theoretical analysis beyond the straightforward MD simulation under the plain DC-DFTB potential energy surfaces (PES). For example, timescale of DC-DFTB-based MD simulation is typically limited within nanoseconds, which makes it difficult to study chemical reactions with high energy barrier and to sample slow motion events including protein folding and arrangement of molecular aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…To date, fast large‐scale chemical reaction simulations combining DFTB with DC have been demonstrated for MD [ 57–64 ] and MetaD [ 65,66 ] (DC‐DFTB‐MD/MetaD). Herein, the extension of DC‐DFTB‐MD/MetaD for running simulations simultaneously for a set of geometries in the same system called walkers or replicas is reported to improve sampling and free energy evaluation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[50,51] Enhanced sampling methods have been recently applied to DFTB-MD, resulting in novel DFTB-REMD, [52] DFTB-REUS, [53,54] and DFTB-MetaD methods. [55,56] To date, fast large-scale chemical reaction simulations combining DFTB with DC have been demonstrated for MD [57][58][59][60][61][62][63][64] and MetaD [65,66] (DC-DFTB-MD/MetaD). Herein, the extension of DC-DFTB-MD/MetaD for running simulations simultaneously for a set of geometries in the same system called walkers or replicas is reported to improve sampling and free energy evaluation efficiency.…”
mentioning
confidence: 99%